Comics for film, games, and animation : using comics to construct your transmedia storyworld - Weaver, Tyler, 1981- (Focal Press, 2013)
Tyler Weaver teaches you how to integrate comic storytelling into your own transmedia work by exploring their past, present, and future. He discusses the creation of the unique mythologies in comic stories and digs into the details of comic construction, from pacing to scripting to collaboration.